The Effect of Aloe Vera, Vitamin C and E on Tumour Marker Enzymes in Hepatocarcinogenesis - Md Akim, Abdah (1998)
The effects of Aloe vera (AV), vitamin C (VC), alpha-tocopherol (T) and gamma-tocotrienol (E) on the activities of six tumour marker enzymes; alkaline phosphatase (ALP), glutathione-S-transferase (GST), gamma-glutamyl transferase (GGT), glutathione peroxidase (GPx), glutathione reductase (GRx) and uridyl diphosphoglucuronyl transferase (UDPGT) in rat liver carcinogenesis were studied. Liver cancer was induced by diethylnitrosamine (DEN) and 2 -acetylaminofluorene (AAF) followed by partial hepatectomy. Ninety male rats (Rattus norwegicus, 120- 150g, 6-7 weeks old) were divided into 15 groups. Six groups comprised the normal and supplemented-control groups. Hepatocarcinogenesis was induced in the other nine groups. Four groups were supplemented with AV, VC, E and T respectively and the other 4 groups were given TNC, T/AV, ENC and E/AV respectively. The last group remained as the cancer-control group. Aloe vera and vitamin C were administered ad libitum at doses of 0.1 mg/L water and 41.7 mg/L water respectively, in both control and cancer groups. Alphatocopherol and gamma-tocotrienol were administered at a dose of 34 mglkg diet and 30 mglkg diet, respectively. The rats were sacrificed by cervical dislocation after 16 weeks. An increase (p<0.05) in all six tumour marker enzymes was observed in the cancer-treated group compared to the normal-control group. Aloe vera supplementation significantly (p<0.05) decreased the tumour marker enzyme activities in cancer-induced liver compared to the cancer-control group. Gammatocotrienol exerted a better effect than alpha-tocopherol in reducing the enzyme activities in cancer-induced liver. Vitamin C significantly (p<0.05) decreased the enzyme activities in GPx, GRx, GST and UDPGT. However, non of the supplementations decreased the alkaline phosphatase activity in the liver cancer.